Associations of self-reported smoking, cotinine levels and epigenetic smoking indicators with oxidative stress among older adults: a population-based study - Gao, X.; Gao, X.; Y. Zhang; Breitling, L. P.; Schottker, B.; Brenner, H. (Eur J Epidemiol, 2017)
Tobacco smoking and oxidative stress (OS) are both related to a wide spectrum of adverse age-related health outcomes, but their association is not yet well-established. We examined the associations of self-reported smoking indicators, serum cotinine levels and smoking-related DNA methylation biomarkers with two urinary proxy markers of OS, 8-isoprostane (8-iso) and 8-hydroxy-2'-deoxyguanosine (8-oxodG), in two independent subsets of older adults recruited in Germany (discovery set: n = 978, validation set: n = 531). We obtained DNA methylation profiles in whole blood samples by Illumina Human Methylation450K Beadchip and measured the urinary levels of both OS markers using commercial ELISA kits. After controlling for potential confounders, current smoking, cumulative smoking exposure (pack-years) and serum cotinine levels (ng/ml) were strongly associated with 8-iso levels (p values <0.0001, 0.004 and 0.001, respectively). Of 151 previously identified smoking-related CpG sites, 71 loci were associated with 8-iso levels after correction for multiple testing (FDR < 0.05) in the validation phase and were designated as loci related to 8-iso levels defined OS. In addition, serum cotinine levels, cumulative smoking exposure and a smoking index (SI) based on the 71 identified loci manifested monotonic associations with 8-iso levels. However, we did not observe any associations between these smoking indicators and 8-oxodG levels. In conclusion, this study suggests that smoking-related epigenetic alterations are closely correlated with smoking-induced OS. The identified CpG sites could potentially be prognostic epigenetic markers of OS and OS-related health outcomes. Our findings and the underlying mechanisms should be followed up in further, preferably longitudinal studies.
Keywords: 8-Hydroxy-2'-Deoxyguanosine Aged Aged; 80 and over Aging Biomarkers/blood Cotinine/*blood DNA/*blood *DNA Methylation Deoxyguanosine/*analogs & derivatives/genetics/urine Dinoprost/*analogs & derivatives/genetics/urine Epigenomics Female Germany/epidemiology Humans Male Middle Aged Oxidative